Sulfonated resorcinol-formaldehyde microspheres as high-capacity regenerable adsorbent for the removal of organic dyes from water. Issue 5 (October 2017) - Islam, Md. Tariqul; Hernandez, Cesar; Ahsan, Md. Ariful; Pardo, Andrew; Wang, Huiyao; Noveron, Juan C.
Graphical abstract: Synthesis of high-capacity and regenerable adsorbent based on sulfonated resorcinol-formaldehyde microspheres for the removal of organic dyes from water. Abstract: In this study, the preparation of sulfonated resorcinol-formaldehyde (RF-SO3 H) microspheres having high adsorption capacity towards organic dyes is reported. The ability for facile regeneration of the RF-SO3 H microspheres is also demonstrated, which may allow for the re-use of the adsorbent as well the re-utilization of the dyes. The RF-SO3 H microspheres exhibited high adsorption capacity towards the anionic and cationic organic dyes such as methyl orange (MO) and methylene blue (MB) from the water. The equilibrium adsorption capacity was measured to be 710 mg/g and 511 mg/g towards MO, and MB, respectively. The effect of pH, contact time, and initial concentration of dyes was analyzed and shown that the adsorption capacity for MO increases in acidic pH and vice versa for MB. The adsorption of MO and MB from tap water was also performed and shown to maintain similar adsorption capacity as in the deionized water. In addition, a packed glass column was prepared to demonstrate the continuous adsorption of MO and MB under flow conditions. Regeneration of the column was achieved by using organic solvents and it was demonstrated that the adsorbent not only recovered but also increased its adsorption capacity after every time it was regenerated.